(untitled) (Journal of the College of Basic Education, 2025)
The research aims to identify "the impact of the R.E.A.C.T. strategy on the achievement of fifth-grade female students in science." From this, the following null hypothesis was derived: "There is no statistically significant difference at a significance level of (0.05) between the average scores of students in the experimental group who studied according to the R.E.A.C.T. strategy and the average scores of students in the control group who studied according to the traditional method on the achievement test." The researchers adopted the experimental design with two groups, experimental and control, with a post-test for achievement. The research community represented all fifth-grade primary school students in government primary schools in Baghdad Governorate/Al-Rusafa II for the academic year (2023-2024) AD. The research sample was chosen intentionally, and consisted of (60) female students from (Al-Zayzafoun Elementary School) who were distributed into two groups, experimental and control. The number of female students in the experimental group was (30) female students and the number of female students in the control group was (30) female students. Equivalence was conducted between the students of the two research groups according to the following variables: (previous achievement in science for the fourth grade, previous information in science, intelligence). The experiment was conducted in the first semester of the academic year (2023-2024) AD. The subject matter that was studied during the experiment period was determined as the first three units of the science book for the fifth grade of primary school. The behavioral objectives for the topics that would be studied were formulated, amounting to (175) behavioral objectives according to Bloom’s levels (remembering, comprehension, application, analysis). To achieve the research objective, the researchers prepared the research tool, which was a multiple-choice achievement test for the science subject, consisting of (40) objective paragraphs with four alternatives. Its validity was confirmed, and the difficulty factor for its paragraphs, the discriminating power, and the effectiveness of its alternatives were extracted. Its stability was confirmed by the two methods of splitting half, as it reached (0.82) before correction and (0.90) after correction, and by the (Kuder-Richardson 20) method, as it reached (0.86). The researchers used appropriate statistical methods and the results showed that the experimental group students who studied according to the R.E.A.C.T strategy outperformed the control group students who studied according to the traditional method in achievement. In light of the results of the current research, the researchers reached a number of conclusions and presented a number of recommendations and proposals.